DYNAMICS OF VILLAGE FINANCIAL MANAGEMENT: DRAMATURGY PERSPECTIVE - Tyas Dyah Fatmawati, Whedy Prasetyo & Siti Maria Wardayati (International Journal of Research Science and Management, 2018)
Installation of APBDesa banners is an effort to realize transparency in use of the budget by village government to village community. Banner orderly administration shows that village government will carry out village government that is clean and no corruption. The banner become a face for village government effort to manage good village financial management in eyes of community. The village community voiced an allegation of a mismatch of activities which written in banner with their realization. Banners become a self-image for village government. That must be consistently displayed so village government can achieve its goal of implementing the transparenct principle properly. This study aims to understanding of dynamics of inconsistency village fund management in S village. Dramaturgy perspective used in this study expected to provide an overview of head village and his apparatus behavior in dealing with dynamics of village fund management. This research was carried out in S village in S sub-district, Banyuwangi Regency. Type of data used in this study is secondary data and primary data. S village government tries to maintain the mandate by carrying out each activity as planned. But obstacles on the fields often make village government did different decisions.